Design and experimental validation of a temperature-driven adaptive phononic crystal slab. (1st February 2019) - Billon, K; Ouisse, M; Sadoulet-Reboul, E; Collet, M; Butaud, P; Chevallier, G; Khelif, A
Abstract: In this paper, an adaptive phononic crystal slab based on the combination of metallic parts and highly dissipative polymeric interfaces is designed. Cylindrical pillars are composed of shape memory polymer and aluminium deposited periodically on the aluminium slab. The mechanical properties of the polymer depend on both temperature and frequency and can radically change from glassy to rubbery state, with various combinations of high/low stiffness and high/low dissipation. A 3D finite element model of the cell is developed for the design of the metamaterial. The shifted-cell operator technique is used to correctly handle damping effects in the dispersion analysis. In order to validate the design and the adaptive character of the metamaterial, results issued from a full 3D model of a finite structure embedding an interface composed by a distributed set of the unit cells are presented. Various driving temperatures are used to change the behaviour of the system, and numerical results obtained on the adaptive structure are compared to experimental ones. Two states are obtained by changing the temperature of the polymeric interface: at 25 °C a bandgap is visible around a selected resonance frequency, and it does not exist anymore above the glass transition temperature, where the phononic crystal slab tends to behave as an homogeneous plate. Numerical and experimental results show energy propagation along the borders of the slab in the bandgap.